A Randomized Placebo-Controlled Study on the Effectiveness of the “Three Good Things for Others” Intervention - Laguna, Mariola; Kȩdra, Michał; Mazur-Socha, Zofia (Frontiers in Psychology, 2021)
The aim of our study was to test the effectiveness of the “three good things for others” intervention. We used the randomized controlled trial method, with four measurements (pretest, posttest, follow-up after two weeks, follow-up after four weeks) and with random assignment of participants to experimental and placebo control groups. We investigated the effects of the intervention on prosocial behavior, and in addition on positive and negative affect, and positive orientation (a general tendency to approach reality in a positive way). The results showed an increase in positive affect and a decrease in negative affect in the experimental group a day after the intervention. These effects, however, did not endure over the next two or four weeks. We also observed a statistically significant increase in prosocial behavior in the placebo control group, in which participants engaged in a task of recalling childhood memories. The results are discussed and recommendations for future studies are proposed.